HBsAg Status, Molecular Detection and Therapy Evaluation of Hepatitis B Patient - Djuma, Agustina W.; Dewu, Sherly; Banunu, Ayorince Herlinalt Gloria; Kambuno, Norma T.; Astuti, Aldiana (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The management of chronic hepatitis B involves various therapeutic approaches, including nucleotide analogs (NUCs) and pegylated-interferon alpha (peg-IFN), either in isolation or in combination. Reverse transcriptase enzyme is competitively inhibited by NUCs, which effectively suppresses HBV replication and lowers viral load. Concerning their cost-effectiveness, high response rates, low side effects, and oral administration, NUCs are recommended. Prolonged use, particularly of NUCs with a low genetic barrier or as monotherapy, can, however, lead to resistance, long-term safety issues, and the need for ongoing treatment. Physicians and other healthcare professionals are extremely concerned about the emergence of resistance and possible safety concerns related to the long-term use of NUCs. Moreover, the requirement for continuous therapy presents notable obstacles concerning patient adherence, distribution of healthcare resources, and overall economic viability. To clarify these problems and direct the creation of more potent and long-lasting treatment plans for chronic hepatitis B, urgent research is required. Hepatitis B surface antigen (HBsAg) detection is frequently accomplished via the use of the Chemiluminescent Microparticle Immunoassay (CMIA), which is a crucial early serologic marker for screening and diagnosis. Polymerase chain reaction (PCR) molecular testing is employed to confirm the presence of HBsAg. Polymerase Chain Reaction (PCR) was the technique we utilized to verify the outcomes. Twenty-eight of the HBsAg-positive patients at W.Z. Johannes Kupang Hospital had positive PCR results, highlighting the significance of molecular confirmation. The results of this study emphasize the value of precise HBsAg testing and the supplementary function of molecular confirmation in the treatment of patients with chronic hepatitis B. Furthermore, it clarifies the current therapeutic approaches applied to this patient population, highlighting the necessity of customized therapeutic approaches based on each patient's unique profile and potential complications.